Outsourcing in innovative activity of the enterprises of the Russian Federation (Путеводитель предпринимателя, 2020)
Perfection of a control system by the organizations in market conditions new to Russia shows increased requirements to management of efficiency of development and outsourcing use at the country enterprises. The given statement is proved by that outsourcing mentions practically all industrial and business processes are modern the enterprises, promotes working out of innovative production and decrease in its final cost price, doing its competitive.